COMPROMISING BETWEEN THE GENERAL AND SPECIFIC IN EAP SYLLABUS DEVELOPMENT IN INDONESIAN CONTEXT - Jamilah, Jamilah (Diksi, 2018)
Abstract(Title: Compromising Between the General and Specific in EAP Syllabus Development in Indonesian Context). The quality of a language program is reflected in the syllabus used from which the aim, contents and belief about language instruction are revealed. Syllabuses for English for Academic Purposes in Indonesian universities have been developed, yet they are not quite satisfactory. This article is to explain how to develop a sound syllabus for EAP in Indonesian context, following the steps: context and needs analysis and syllabus planning. Data were collected through triangulated survey employing questionnaires, observation, document study and discussion. Research participants were students, English teachers, and management staff of Yogyakarta State University. Integrated, theme-based syllabus is proposed that includes study skills in higher education as the general theme, which is completed with specific themes related to students' disciplines. This way enables both general and specific skills of EAP to be included in a single syllabus. Keyword: syllabus, language program, English for academic purposes, instruction.